Distorted magnetic island formation during slowing down to mode locking in helical plasmas. (12th May 2017) - Tokuzawa, T.; Takemura, Y.; Watanabe, K.W.; Sakakibara, S.; Narushima, Y.; Tsuchiya, H.; Nagayama, Y.; Inagaki, S.; Ida, K.; Yoshinuma, M.; Tanaka, K.; Suzuki, Y.; et al.
Abstract: We report the first observation of the formation of a magnetic island before the occurrence of mode locking in helical plasma. New analysis and observation techniques applied to the ECE signal and poloidal flow in LHD experiments yield the following results. (i) A magnetic island structure is present, rotating at the end of the rotating phase. (ii) The rotation speed of the island is not uniform in space and time. The rotation of the island changes significantly at the end of the rotating phase, and the deformation increases until the mode is locked.